Some basic concepts of wave-particle interactions in collisionless plasmas - Tsurutani, B.T.; Lakhina, G.S. (My University, 1997)
The physical concepts of wave-particle interactions in a collisionless plasma are developed from first principles. Using the Lorentz force, starting with the concepts of particle gyromotion, particle mirroring and the loss cone, normal and anomalous cyclotron resonant interactions, pitch angle scattering, and cross-field diffusion are developed. To aid the reader, graphic illustrations are provided.
Keywords: Wave-particle interactions; Collisionless plasmas